FITOREMEDIASI LIMBAH LAUNDRY MENGGUNAKAN TANAMAN MENSIANG (Actinoscirpus grossus) DAN LEMBANG (Thypa angustifolia L.) - Mohammad Mirwan; Indria Puspita (EnviroUS, 2021)
ABSTRACT Laundry wastewater is one of kind waste in general disposed directly into the environment (sewage) without any treatment. Laundry wastewater contains pollutants including Surfactants, Phosphates, BOD and TSS. Phytoremediation is one of the methods used in laundry wastewater treatment and was tested in this research. The plants used in this method are Mensiang and Lembang. In addition, this research uses a batch system with volume 10 liters and the variation of space between plants are 3 and 5 plants per reactor. The detention time of wastewater in the reactor is 3, 6, and 9 days. The results from this research are percents removal of Surfactant and BOD was 97,26% and 84,94% and it happened on Lembang reactors. Percents removal of Phosphate and TSS was 98,38% and 93,81%, and it happened on Mensiang reactors. The optimum time detention are 9 days.